THE DIFFERENCES OF STUDENT LEARNING MOTIVATION BETWEEN THE COOPERATIVE LEARNING MODEL OF STUDENTS TEAM TYPE ACHIEVMENT DIVISIONS (STAD) AND JIGSAW TYPE IN BASIC ACCOUNTING STUDY IN CLASS X IN SMK NEGERI 3 DEPOK - Salsabila, Ainiyah; Sumiati, Ati; Zulaihati, Sri (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2020)
This study aims to determine the differences in student learning motivation taught by cooperative learningmodel type Student Team Achievement Divisions (STAD) and Jigsaw type in basic accounting subjectfor class X at SMK Negeri 3 Depok. This research is an experimental research with a pure research design. Thesample of this study was 69 students in class X Accounting at SMK Negeri 3 Depok. Based on theresults of the data analysis requirements, it states that the two classes are normally distributed and arehomogeneous. The results of the hypothesis test show that there are differences in the average learningmotivation of students who use the Student Team Achievement Divisions (STAD) cooperative learningmodel and the Jigsaw cooperative learning model. where the STAD type of cooperative learning model hasa greater effect than the Jigsaw type on student learning motivation. The novelty of the research is theapplication of a similar learning model but different types, namely the Student Team Achievement Divisions(STAD) cooperative learning model with the Jigsaw type cooperative learning model.